Surprise Luncheon : Modesta Yob feted (Raton Range Raton, New Mexico, 1982)
Newspaper Article on Modesta Yob's retirement from the beauty business.
Master list item #: 3
File location is in the Raton File Cabinet
Keywords: Yob, Modesta; Schulte, Erma; Arcangeli, Emma; Ghiglieri, Alma; Kolb, Jewel; Mangini, Isabel; Langston, Ruth; Pappas, Katherine; Wersonick, Alex; Wersonick, Janet; White, Sam; Segotta, Maxine; McKinley, Kathleen; Sweet Shop; Dawson High School; Bon Ton Beauty School; Modesta's Beauty Shop; Local History; Biography; Life and Customs; Retirement; Beauty Shop; Luncheon; Celebration; Raton, New Mexico; Denver, Colorado; Dawson, New Mexico